Plumbagin induces G2/M arrest and apoptosis and ferroptosis via ROS/p38 MAPK pathway in human osteosarcoma cells - Jintang Li; Hang Gao; Ping Wang; Chao Sun; Zhilin Wei; Xingcheng Yi; Shuyuan Yu; Yanan Zhang; Shuqiang Li (Alexandria Engineering Journal, 2024)
Plumbagin (PLB), a naphthoquinone compound, has been proven to have anti-cancer properties in different types of cancers. However, the anti-tumor actions as well as molecular processes in osteosarcoma (OS) remain unclear. This study investigates the underlying mechanisms of PLB in human OS cells in vitro. Our study showed that PLB significantly inhibited the proliferation of human OS cells in a time- and dosage-dependent manner. RNA sequencing data revealed that the efficacy of PLB is related to cell cycle, cell death, and p38 MAPK signaling pathway in KHOS-240S cells. Further studies indicated that PLB triggers G2/M phase arrest, mitochondrial-dependent apoptosis, as well as ferroptosis in human OS cells. Mechanistically, PLB treatment increased ROS generation that activates the p38 MAPK signaling pathway. BIRB 796, a p38 MAPK inhibitor, partly reversed PLB-induced phase arrest of G2/M and cell death. Furthermore, N-acetylcysteine (NAC), a ROS scavenger, significantly decreased G2/M phase arrest and cell death and reversed p38 MAPK activation caused by PLB. In conclusion, PLB induces arrest G2/M arrest, apoptosis as well as ferroptosis in human OS cells via ROS generation and p38 MAPK activation. There is potential for PLB to be an effective treatment for OS.